Pengetahuan Dan Praktik Bidan dalam Menerapkan Respectful Maternity Care Pada Pelayanan Anc: Systematic Literature Review - Apria Hartina Aghna; Endang Surani (Journal of Medical Practice and Research, 2026)
This study aimed to systematically synthesize evidence regarding midwives’ knowledge and practices in implementing Respectful Maternity Care (RMC) within antenatal care (ANC) services. A non-empirical approach using a systematic literature review was conducted by analyzing peer-reviewed articles retrieved from major international databases, guided by the PICO framework and PRISMA protocol. The findings indicate that midwives generally demonstrate moderate levels of knowledge regarding RMC, yet this understanding does not consistently translate into respectful clinical practices. Variability in implementation is influenced by interpersonal competencies, professional values, and contextual constraints within healthcare systems. Evidence also reveals that structural determinants, including institutional policies, resource availability, and organizational culture, significantly shape the extent to which RMC principles are applied in routine care. Moreover, women’s preferences for more personalized and respectful services highlight the importance of relational dimensions in maternal healthcare. These findings underscore the need for integrated strategies that combine continuous professional education, ethical reinforcement, and systemic reform to ensure the consistent application of RMC. Strengthening these dimensions is essential for improving maternal care quality and advancing global maternal health outcomes.